Managing coastal pelagic fisheries: A case study of the small-scale purse seine fishery in Kenya. (15th July 2017) - Okemwa, Gladys M.; Maina, George W.; Munga, Cosmas N.; Mueni, Elizabeth; Barabara, Mwaka S.; Ndegwa, Stephen; Thoya, Pascal; Ntheketha, Nicholas
Abstract: Balancing sustainability and conservation concerns with the socioeconomic needs of small-scale fishers is a dilemma that is commonly faced by fisheries managers. In this paper, we present a case study on managing the developing small-scale purse seine (or ring net) fishery introduced to Kenya by migrant fishers. The fishery, which primarily targets coastal pelagics in offshore waters, was deduced to have the potential of reducing fishing effort on nearshore demersal reef fish stocks while enhancing fisheries production and fisher livelihoods. The expanding fishery elicited much controversy resulting in resource use conflicts related to gear competition and concerns about the environmental impacts of the gear. We detail the consultative planning process that was undertaken to develop a gear-based management plan spanning over 10 years from 2004 to 2016. We briefly document the catch dynamics and evolution of the fishery, and further detail the challenges and key outcomes of the decision-making process. Regulatory measures agreed by stakeholders include restrictions on gear dimensions as well as spatial restrictions defining the distance and depth of operation. Effective implementation and enforcement of the measures will require collective action from all stakeholders. Future considerations should focus on harmonization of proposed measures in transboundary areas. Highlights: The planning process can be challenged by limited resources and bureaucracy. Resource use conflicts can arise due to divergent opinions. The key lessons learned include: Regular feedback to stakeholders and a committed technical team. Close monitoring and institution of precautionary and adaptive measures.